Prognostic and clinicopathological role of long non-coding RNA taurine upregulated 1 in various human malignancies: A systemic review and meta-analysis - Xiaoxiong Wang; Xin Chen; Daming Zhang; Guang Yang; Zhao Yang; Zhiqin Yin; Shiguang Zhao (Tumor Biology)
The aberrant dysregulation of taurine upregulated 1, a novel discovered long non-coding RNA, was ubiquitous in different human solid tumors. Accumulating researches have indicated that taurine upregulated 1 is an independent prognostic indicator in cancer patients. This investigation aimed to further explore the prognostic and clinical significance of taurine upregulated 1 in various types of cancers. Eligible studies were systematically searched in PubMed, Embase, Medline, and Web of Science databases. A total of 12/14 studies with 1303/1228 individuals were included to evaluate the association of taurine upregulated 1 with overall survival and clinicopathological features by pooled hazard ratio and odds ratio in malignancies. The meta-analysis suggested overexpression of taurine upregulated 1 was significantly correlated with unfavorable overall survival in patients with cancer (pooled hazard ratio = 1.63, 95% confidence interval: 1.29–2.06). There was also a significantly positive correlation between high level of taurine upregulated 1 and high pathological grade carcinoma (pooled odds ratio = 4.41, 95% confidence interval: 3.07–6.43) and positive lymphatic metastasis (pooled odds ratio = 2.00, 95% confidence interval: 1.31–3.06). In summary, upregulated taurine upregulated 1 is correlated with more advanced clinicopathological characteristics and poor prognosis, suggesting that taurine upregulated 1 may serve as a novel predictive biomarker of patients with numerous tumors.